Impact of health systems interventions in primary health settings on type 2 diabetes care and health outcomes among adults in West Africa: A systematic review - Eugene Paa Kofi Bondzie; Kezia Amarteyfio; Yasmin Jahan; Nana Efua Enyimayew Afun; Mary Pomaa Agyekum; Ludovic Tapsoba; Dina Balabanova; Tolib Mirzoev; Irene Agyepong (PLoS ONE, 2025)
Type 2 diabetes is ambulatory care sensitive and adequate outpatient primary care supported by strong functional health systems can reduce avoidable complications and related mortality. A large body of published evidence exists on pharmacological agents and non- pharmacological interventions for the management of type 2 diabetes. However, the evidence on health systems’ ability to support patients’ primary care needs, especially in West Africa, where non-communicable disease (NCD) is an increasingly important part of the disease burden is uncertain. This systematic review explores the current published evidence on health systems interventions to support primary health facilities for type 2 diabetes care and impact on health outcomes, service access and quality in West Africa. The World Health Organization health systems building blocks and other post building blocks health systems frameworks guided our search and analysis. Only three pilot studies, including two randomized controlled trials and one pre-post study, met all our first inclusion criteria. However, we included 12 other studies which did not meet all the inclusion criteria but reported on a health system intervention for complete analysis: (The criteria were expanded to include studies conducted outside primary care settings. The rationale was that findings from such studies may influence primary care. Also, non-randomized control trials were later included). Our results showed that interventions with significant impact on glycemic control, treatment adherence, health literacy, and other associated outcomes addressed intersections between the individual health system blocks/areas. Thus, four cross-cutting themes related to the building blocks were found during analysis. The first theme was on interventions targeting the availability of trained health workers and the quality of their services; the second was on interventions targeting institutional infrastructure and resources for management; the third was on interventions targeting leadership and organizational culture and; the fourth was interventions targeting relationships among stakeholders. A fifth theme highlighting patients and family empowerment for type 2 diabetes control was also found in most of the interventions. Conclusion These findings confirm that the rising burden of non-communicable diseases in West Africa, particularly type 2 diabetes, can be tackled by strong functional primary healthcare systems.